APPLICATION OF THE VIKOR METHOD FOR THE BEST JOB SEEKERS RECOMMENDATION (CASE STUDY: PT PLN RIAU AND RIAU ISLANDS REGION) - Sukamto Sukamto; Riki Ario Nugroho; Chairia Octaviani (Informatika, Universitas Jenderal Soedirman, 2022)
PT. PLN (Persero) in serving the community requires quality human resources. The quality of employees in supporting the advancement of a company is very important, so many companies are trying to have quality employees. The way that can be done is by recruiting prospective job seekers according to the criteria desired by the company. The VIKOR method is a ranking method using a multi-criteria ranking index based on a certain measure of proximity to the ideal solution. The alternative consists of 10 job seekers, with the criteria used are Endurance tests, academic tests, psychological tests, laboratory tests and interview tests. The final result is to provide recommendations for the five best job seekers in the order of AB, AC, AD, AF and AG.